Evaluating the Effects of Biodegradable and Conventional Modified Atmosphere Packaging on the Shelf Life of Organic Cavendish Bananas - Rahaman, Adams Abdul (Journal of Postharvest Technology, 2013)
The physiological disorders in banana fruits result in the reduction of fruit quality and the market value that can manifest as diseases in consumer packages. This study investigates the effects of the use of Biodegradable (Bioflex) Modified Atmosphere Packaging (MAP) and LDPE Conventional MAP on rate of ripening (colour changes) and overall consumer acceptance of Cavendish banana fruits at 20°C and 80% RH for eight days. Banana fruits stored in Biodegradable MAP showed quite lower weight loss as compared to others. Fruits stored in Conventional MAP and without Package ripened rapidly as compared with Biodegradable MAP. The CO2 concentration for the Biodegradable MAP and Conventional MAP were 12% and 9.8% respectively. The O2 Concentration decline gradually to 5.2% for Biodegradable MAP compared with 2% for the Conventional MAP. Moreover, fruits stored in Biodegradable MAP showed superior consumer acceptability.